Combat-Acquired Traumatic Brain Injury, Posttraumatic Stress Disorder, and Their Relative Associations With Postdeployment Binge Drinking. Issue 1 (January 2016) - Adams, Rachel Sayko; Larson, Mary Jo; Corrigan, John D.; Ritter, Grant A.; Horgan, Constance M.; Bray, Robert M.; Williams, Thomas V.
Abstract : Objective: To examine whether experiencing a traumatic brain injury (TBI) on a recent combat deployment was associated with postdeployment binge drinking, independent of posttraumatic stress disorder (PTSD). Methods: Using the 2008 Department of Defense Survey of Health Related Behaviors among Active Duty Military Personnel, an anonymous survey completed by 28 546 personnel, the study sample included 6824 personnel who had a combat deployment in the past year. Path analysis was used to examine whether PTSD accounted for the total association between TBI and binge drinking. Main Measures: The dependent variable, binge drinking days, was an ordinal measure capturing the number of times personnel drank 5+ drinks on one occasion (4+ for women) in the past month. Traumatic brain injury level captured the severity of TBI after a combat injury event exposure: TBI-AC (altered consciousness only), TBI-LOC of 20 or less (loss of consciousness up to 20 minutes), and TBI-LOC of more than 20 (loss of consciousness >20 minutes). A PTSD–positive screen relied on the standard diagnostic cutoff of 50+ on the PTSD Checklist-Civilian. Results: The final path model found that while the direct effect of TBI (0.097) on binge drinking was smaller than that of PTSD (0.156), both were significant. Almost 70% of the total effect of TBI on binge drinking was from the direct effect; only 30% represented the indirect effect through PTSD. Conclusion: Further research is needed to replicate these findings and to understand the underlying mechanisms that explain the relationship between TBI and increased postdeployment drinking. Abstract : Supplemental Digital Content is Available in the Text.